Socialization Tactics, Self-Efficacy, and Newcomers' Adjustments to Organizations - Jones, Gareth R. (Academy of Management Journal, 1986)
This study investigated the relationship between the socialization tactics employed by organizations and a series of role and personal outcomes. It also examined the effects of self-efficacy on role orientation. Consistent with predictions, results suggest that different patterns of socialization lead to different forms of newcomer adjustment to organizations. Specifically, institutionalized tactics lead to custodial role orientations, and individualized tactics to innovative role orientations. The results also suggest that self-efficacy moderates this learning process-specifically that socialization tactics produce a stronger custodial role orientation when newcomers possess low levels of self-efficacy.